2017
DOI: 10.3892/mmr.2017.6277
|View full text |Cite
|
Sign up to set email alerts
|

Role of hypoxia-inducible factor-1α in autophagic cell death in microglial cells induced by hypoxia

Abstract: Microglial cells are phagocytic cells of the central nervous system (CNS) and have been proposed to be a primary component of the innate immune response and maintain efficient CNS homeostasis. Microglial cells are activated during various phases of tissue repair and participate in various pathological conditions in the CNS. Following spinal cord injury (SCI), anoxemia is a key problem that results in tissue destruction. Hypoxia-inducible factor 1-α (HIF-1α) may protect hypoxic cells from apoptosis or necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 59 publications
(54 reference statements)
2
26
0
Order By: Relevance
“…Factors such as free radicals, glutamate, tumour necrosis factor (TNF), ischemia, and hypoxia cause delayed neuronal death (Oyinbo, 2011;Zhang et al, 2012). Studies have reported that anoxemia after SCI leads to tissue destruction, while hypoxia gradually induces cell death alongside inflammation (Wang et al, 2017). Other data indicate that anoxemia also can lead to a variety of vascular pathologies that lead to acute arterial occlusion, ischemia, and shock (Fleming et al, 2006;Webb et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as free radicals, glutamate, tumour necrosis factor (TNF), ischemia, and hypoxia cause delayed neuronal death (Oyinbo, 2011;Zhang et al, 2012). Studies have reported that anoxemia after SCI leads to tissue destruction, while hypoxia gradually induces cell death alongside inflammation (Wang et al, 2017). Other data indicate that anoxemia also can lead to a variety of vascular pathologies that lead to acute arterial occlusion, ischemia, and shock (Fleming et al, 2006;Webb et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…All reagents and chemicals were purchased and used directly without further purification. The bone marrow stromal cell line was collected from the rat model of our team (28)(29)(30), whilst the BV-2 microglial cell line was provided by CHI Scientific Inc. (cat. no.…”
Section: Methodsmentioning
confidence: 99%
“…The fixative was removed, the sample was rinsed three times with PBS and fixed with 1% osmic acid solution for 2 h at 37˚C. The sample was subsequently dehydrated using an ascending ethanol gradient (30,50,70,80, 90 and 95%) and treated with pure acetone for 20 min at 25˚C. The sample was treated with a mixture of epikote resin and acetone (v/v=1/1) for 1 h, followed by the same mixture but at a higher concentration of the embedding agent (v/v=3/1) for 3 h before incubation with 100% embedding agent overnight at 25˚C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations